Tawhid dalam Pemikiran Hamka - Delavia Andrea Fererli; Amril Amril (Jurnal Kawakib, 2026)
This study examines the concept of tawhid in Hamka’s thought and its relevance in addressing contemporary Islamic conservatism, which is characterized by textualism, resistance to rational and contextual interpretation, and exclusivism. Using a qualitative approach through literature review and content analysis of Hamka’s works, this study finds that tawhid is not merely theological but also encompasses rational, ethical, and social dimensions. It functions as an integrative principle that unifies faith, reason, and action. In this context, tawhid offers a offers a critical alternative framework by strengthening the role of reason, rejecting exclusive truth claims, and emphasizing ethical values in social life. Therefore, tawhid in Hamka’s thought provides a foundation for a more rational, open, and contextual understanding of religion, highlighting its relevance as a transformative response to contemporary conservatism.